Deficiency of dltD contributes to increased autolysis in Streptococcus mutans - Jingyun Du; Shan Huang; Yijun Li; Minjing Wu; Shuai Chen; Ling Zhan; Xiaojing Huang (Journal of Oral Microbiology)
Streptococcus mutans (S. mutans) is one of the major etiological agents of dental caries. Interfering with the expression of genes associated with cariogenicity of S. mutans is an effective ecological approach for caries prevention. Thus, understanding the role of genes related to cariogenicity in S. mutans is important. dltD is a conserved gene in Gram-positive bacteria, which is involved in D-alanylation of lipoteichoic acid to modify cell surface charge. In vivo caries experiments have shown significant decreases in the caries severity in rats infected with S. mutans dltD-deficient strain. Although the impact of dltD on bacterial surface charge and division in other Gram-positive bacteria is known, its role in S. mutans biological functions remains unclear. This study aimed to investigate the biological functions of dltD in S. mutans. We examined growth curves, morphology, autolysis, biofilm formation, and cell membrane properties of S. mutans wild strain and dltD-deficient strain. Our results revealed that dltD plays a key role in the growth and autolysis of S. mutans. dltD deletion increased biofilm autolysis, thereby reducing the number of viable bacteria within the biofilm. Furthermore, dltD may have an epistatic effect on cell division and surface charge. Its regulatory network needs to be further elucidated. This study shed light on therole of dltD in the growth of S. mutans, thereby enhancing our understanding of its function.